Penerapan Qawaid Fiqhiyah dalam Letter of Credit (LC): Telaah Hukum Islam Terhadap Instrumen Pembiayaan Perdagangan - Imam Kamaluddin; Noval Hasbi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Export and import activities are one of the activities that greatly influence economic activities in a country, but in its sustainability there are several risks and challenges that must be faced by importers and exporters, especially in transaction activities, a country and financial institutions have a role to reduce the risk, one way is by using a Letter of credit, therefore the purpose of this study is to find out how the review of Legal Maxim on Letter of credit transactions contains several risks and benefits in its sustainability. This study uses field research and is included in library research where Legal Maxim is the main method in reviewing the risks and benefits of letters of credit. The results of this study indicate that in import and export transactions it is permissible to use it if it is necessary for business actors and if it causes many benefits to the community, but in terms of the risks faced, the state, financial institutions and business actors have a very large role in minimizing the occurrence of these risks in the sustainability of Letter of credit transactions.